Experimental study of volume speckle in four-wave mixing arrangement - Salazar, Angel (2003)
We study a high frequency modulated speckle pattern in a four-wave mixing arrangement. The three-dimensional nature of the speckles is considered in the phase conjugate reflectivity evaluation which implies to analyze its dependence on the average speckle size. Also, the reflectivity is analyzed in terms of the external applied field, the probe beam ratio, and the pupil aperture diameter of the imaging system that generates the subjective speckle beam.